Pemantauan Status Gizi Balita Melalui Peningkatan Kegiatan Posyandu Harapan Ibu 6, Kelurahan Mata Air Kota Padang - Yeffi Masnarivan; Rahmi Awalina; Resmiati Resmiati (Warta Pengabdian Andalas, 2023)
Stunting is a major nutritional problem in Indonesia because it will have a long-term impact on the quality of human resources. Stunting impacts intelligence levels' susceptibility to disease and reduces productivity, hampering economic growth and increasing poverty and inequality in the future. This community service activity was carried out in the form of active involvement in Integrated Healthcare Center activities in July 2023. The method used monitoring, counselling, and intervention methods for toddlers. Respondents were taken by total sampling: all toddlers in the working area of ​​Posyandu Harapan Ibu 6. Based on the results of monitoring the nutritional status of the 64 toddlers, about 62.5% have had standard nutritional status, and 37.5% have nutritional problems. There are seven toddlers (10.9%) experienced stunting, two toddlers (3.1%) had poor nutritional status, 15 toddlers (23.4%) experienced malnutrition, eight toddlers (12.5%) experienced underweight, and two toddlers (3.1%) experienced the most underweight. All cadres of health care and the local government welcomed this community service activity. It was recommended that cadres consistently innovate in implementing and monitoring toddlers' nutritional status to increase mothers' awareness about stunting impacts.